Pemenuhan Hak Layanan Kesehatan Dan Makanan Bagi Narapidana Hamil Di Lembaga Pemasyarakatan - Subroto, Mitro; Admirad, Keny (Peneliti.net, 2025)
In modern correctional systems, the concept of human rights has evolved to ensure that all individuals, including those incarcerated, receive humane and fair treatment. This includes the right to health, which encompasses access to adequate healthcare and nutritious food, critical for pregnant inmates due to their unique physical and psychological needs. Despite these principles, implementation often faces challenges such as limited resources and social stigma. Research reveals obstacles like inadequate health facilities and insufficient nutritional provisions. While legal frameworks, such as the 1945 Indonesian Constitution and international agreements like ICCPR and CEDAW, affirm the protection of health rights, gaps remain in practice. The consequences of unmet health and nutrition needs can be severe, impacting both the mother and child. Correctional institutions in Indonesia have made efforts to improve healthcare services, but significant gaps persist. This study employs a qualitative case study approach to investigate the factors affecting the fulfillment of health and nutritional rights for pregnant inmates, assess existing policies, and identify challenges. The findings aim to offer a comprehensive overview and recommendations for improving healthcare and nutritional services, ensuring the full realization of pregnant inmates' human rights.